2018
DOI: 10.1097/md.0000000000012323
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Three-Circle Post Standing (Zhanzhuang) Qigong on the physical and psychological well-being of college students

Abstract: Background:The physical and mental health of college students tends to continuously decline around the world due to lifestyle or behavior habits changes, and pervasive presence of the Internet. Thus it is urgent to improve their health in college life. As a traditional Qigong form is practiced mainly in a standing posture. Three-Circle Post Standing Qigong (TCPSQ) is suitable for regular practicing and has beneficial effects on improving the physiological function and psychological emotion by adjusting body, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 83 publications
0
11
0
Order By: Relevance
“…What is more regrettable is the limited use of evidencebased interventions designed to control symptoms and improve the patient's functions. Qigong therapy, one of the traditional Chinese wellness practices, is a gentle low-impact mind-body aerobic exercise that primarily emphasizes the combination of the "three regulations": body focus (posture and movement), breath focus, and mental focus (meditative components) (23). It is simply referred to as optimizing and restoring the body, mind, and spirit (40).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…What is more regrettable is the limited use of evidencebased interventions designed to control symptoms and improve the patient's functions. Qigong therapy, one of the traditional Chinese wellness practices, is a gentle low-impact mind-body aerobic exercise that primarily emphasizes the combination of the "three regulations": body focus (posture and movement), breath focus, and mental focus (meditative components) (23). It is simply referred to as optimizing and restoring the body, mind, and spirit (40).…”
Section: Discussionmentioning
confidence: 99%
“…It includes eight kinds of massage manipulations on the abdomen and a kind of upper body shaking. Some studies have confirmed the efficacy of massage manipulations for relieving fatigue, sleep quality, and gastrointestinal discomfort (19)(20)(21) and to promote beneficial changes in the central nervous system (CNS) (22,23). Other studies suggest that abdominal massage manipulation therapy can cause physiological, neurological, or psychological responses through the b-endorphin release or catabolite elimination to promote a sense of well-being and pain sensation and fatigue relief (21).…”
Section: Study Protocolmentioning
confidence: 99%
“…As one of representative mindful exercises, CMQ is a famous mind-body aerobic practice which originated from Traditional Chinese Medicine 44 , CMQ has been found to have effects on various conditions, such as to prevent and cure psychological and physical disease. CMQ characteristic with initiative exercises to regulate body, breath, mind and to integrate them into one.…”
Section: Discussionmentioning
confidence: 99%
“…It is characterized by static work as an aid, focusing on the manipulation of the abdomen in terms of breathing and thinking regulation, the main use of normal abdominal breathing, gradually increasing the concentration of thinking in the lower Dantian. 26 More importantly, during a session, the participants can practice while lying down or sitting, completely free from time and space constraints.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence to date supports Qigong's potential benefits of improving depression, quality of life, and motor function in patients with CFS, such as Tai Chi, 23 Baduanjin (also called Eight-Section Brocades, ) 24 and Liuzijue 25 . More importantly, Qigong can promote beneficial changes in the central nervous system (CNS), including favorable changes in the dopaminergic and other neurochemical systems, and depression, anxiety in the sympathetic nervous system (SNS) and/or hypothalamic-pituitaryadrenal axis (HPAA), perceived stress levels, fibromyalgia, pain, and hormonal changes 26,27 . The PLWNT method is a kind of Chinese Qigong, including eight kinds of massage manipulations on the abdomen and a kind of upper body shaking, which can strengthen the connection between the brain and the intestine through the Brain-Gut Axis, and connect the cognitive and emotional centers with the neuroendocrine and intestinal system immunity.…”
Section: Introductionmentioning
confidence: 99%